Development of Green Composite Based on Recycled-Low Density Polyethylene (r-LDPE) as an Environmentally Friendly Packaging - Hamdiani, Saprini; Kamali, Siti Raudhatul; Ismillayli, Nurul; Kurniawati, Lely; Sumarlan, Iwan (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Low-Density Polyethylene (LDPE) is one of the most popular and commonly used petroleum-derived thermoplastics for packaging. The large production of LDPE has an environmental impact. Reducing production can be done by recycling LDPE (r-LDPE) and adding organic fibres as a filler that is easily decomposed. Cattle farming solid waste as a fibre source was mixed with r-LDPE with coupling agent maleic anhydride (MA). Before use, the cow manure was processed through a bleaching and hemicellulose removal process, which resulted in Cow Manure Fiber (CMF). The CMF was analyzed using FTIR spectroscopy and microscopic fibre dimension analysis. The FTIR results showed peaks at wavenumbers 3538 and 1056 cm-1, representing the -OH, -C-O and -CH functional groups from the cellulose structure. The resulting composites were tested for physical properties, including elastic modulus, yield stress, and elongation. Pure LDPE material was also used for comparison. The best physical properties of the composites were obtained by composites with 95% r-LDPE, 5% CMF, and 2% MA.